(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
This article brings phenomenology in dialogue with the performing arts and shows how it can offer new ways of working with intractable problems that negatively affect the health of performers and the vitality of performance. It is based on a paper I presented at the Society for Existential Analysis Seminar on Phenomenology and the Arts held at King’s College London in collaboration with the British Association for Performing Arts Medicine and Professor Daniel Leech-Wilkinson in November 2019.